Senior High School Students Perception on Sustainability Literacy in Biology Learning - Adelia Aryani Putri; Topik Hidayat; Bambang Supriatno (Postgraduate, University of Mataram, 2023)
The Sustainable Development Goals (SDGs) are a global partnership's urgent call to action from all developed and developing countries to build a sustainable future. Students play an essential role in achieving this goal because they are the primary objects of formal education who can be involved through concrete actions and appropriate and effective decision-making. In order to achieve this goal, sustainable development capability and capacity, as measured by sustainability literacy, are required. The purpose of this study is to gather information about students' initial perceptions of environmental change subject in relation to students' sustainability literacy. The method used is a descriptive method with a quantitative approach. This study was conducted in February 2023 on 34 students from grade XI in SMAN 1 Bandung who had already completed the subject. Students' sustainability literacy was assessed using a questionnaire. Descriptive analysis was used to examine the data. Finding indicated that the indicator of knowledge was worth 43% within very bad category, knowledge of skills had a value of 44% with a very bad category as well and mindset was worth 55% with a bad category. As a result, it is possible to conclude that students' sustainability literacy is of very bad quality.